A influência da pesquisa na motivação dos discentes na educação profissional - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This thesis aimed to investigate the use of project methodology (which involves working with research) in a school of Don Pedrito Professional Education / RS, contribute to the motivation of students in Technical Course Administration. It is believed that research encourages the pursuit of solving everyday problems, seeking a better quality of life in society. The research carried out was of great importance, because it favored the understanding of how research influences the motivation of students to complete the Technical Course in Management, as it sought to know how teachers perceive, understand and engage with the methodology used by the school and what aspects make the management team believe and encourage the Project Methodology. The survey was conducted in the first half of 2015 and is in a research qualitative and quantitative nature, taking field research methodology. The research subjects were 16 students of the last semester of the Technical Course in Management, 05 teachers and 03 members of the school management team. The steps for the development of research contemplated the description of how the pedagogical practices involved in project methodology were developed in the course and the search for views of stakeholders regarding this methodology. So, if researched and analyzed the motivation that work with research generated in students. As research instruments were used questionnaires with open and closed questions and interview. In the analysis of the data found, the results indicate that the design methodology used by the school started with formations that were held during the school deployment process and a faculty meeting. According to the management team the Pedagogical Political Project school is under construction, but is now set to will it contain the Project Methodology because the team believes that working with research brings benefits for students because it generates autonomy in the pursuit of learning. n addition, the management team says the Project Methodology requires greater involvement of teachers, promoting these in the evaluation stage of development of students. The students claim that the development of work and research is important as it provides skills, which they consider important both for their training and for personal growth, and the completion of research projects promotes in students the feeling of satisfaction staff. It is concluded that the design methodology influence the motivation of students to complete the course because the research leads these the application of theories in a practical way, motivating them to study and complete their Technical Course Administration.
Keywords: Educação técnica; Metodologia de projetos; Motivação; Professional education; Project methodology; Education; Motivation